Evidence from meta-analysis about parental involvement in education which supports their children's learning. Issue 3 (21st September 2015) - Tracey Bywater, Dr; Higgins, Steven; Katsipataki, Maria
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to contribute to understanding of different ways that parents and schools develop and maintain working partnerships to improve outcomes for children by focusing on quantitative evidence about parental involvement (PI). The key questions for this synthesis are: what is the evidence about the extent of impact of PI on cognitive or academic outcomes for children, and how consistent and reliable is this evidence? Design/methodology/approach – This is an "umbrella" review comparing and contrasting findings from 13 meta-analyses across three areas of PI and home/school partnerships: first, general approaches; second, home and family literacy programmes; and finally, targeted interventions focused on individual or specific family need. Findings – There is consistent evidence about the extent of impact from general approaches (three to six months average additional gain for children's educational outcomes) and for targeted intervention (four to six months), but with a wider range of estimates for family literacy (two to eight months average gain). Variation in approaches and evaluation quality make specific recommendations for practice challenging, though some consistent patterns of findings indicate strategies that are likely to be "good bets" to explore and evaluate. Research limitations/implications – The quality of the underlying studies makes drawing secure implications for practice difficult. The nature of the review means that it does not capture the most recent studies. Originality/value – The paper provides a synthesis of quantitative evidence from 13 meta-analyses to identify where there is consistency in estimates of impact and what is associated with systematic variation in this impact.